The Dangers of Decoupling: The Relationship Between Compliance Programs, Legitimacy Perceptions, and Institutionalized Misconduct - MacLean, Tammy L.; Behnam, Michael (Academy of Management Journal, 2010)
This theory-building analysis spotlights a dynamic that occurs between decoupling, legitimacy, and institutionalized misconduct. Using data gathered from a case study of widespread deceptive sales practices at a large financial services firm, we demonstrate the dangers of decoupling an organizational compliance program from the core business activities of an organization. We illustrate how decoupling created a “legitimacy facade” that enabled the institutionalization of misconduct and precipitated a loss of external legitimacy.